2021
DOI: 10.1007/s10549-020-06039-w
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity during long-term trastuzumab use in patients with HER2-positive metastatic breast cancer: who needs cardiac monitoring?

Abstract: Purpose Patients with HER2-positive metastatic breast cancer (MBC) usually receive many years of trastuzumab treatment. It is unknown whether these patients require continuous left ventricular ejection fraction (LVEF) monitoring. We studied a real-world cohort to identify risk factors for cardiotoxicity to select patients in whom LVEF monitoring could be omitted. Methods We included patients with HER2-positive MBC who received > 1 cycle of trastuzumab-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…In our study, LVD occurred more commonly during the first 4 years of therapy. Our data agree with previous studies on MBC patients [17][18][19][22][23][24] who have documented a higher incidence of CTOX during the first years of treatment. Indeed, CTOX during prolonged trastuzumab therapy showed a plateau phenomenon characterized by a relatively early start of LVD.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, LVD occurred more commonly during the first 4 years of therapy. Our data agree with previous studies on MBC patients [17][18][19][22][23][24] who have documented a higher incidence of CTOX during the first years of treatment. Indeed, CTOX during prolonged trastuzumab therapy showed a plateau phenomenon characterized by a relatively early start of LVD.…”
Section: Discussionsupporting
confidence: 93%
“…In our cohort, older age and longer duration of trastuzumab-based therapy were predictive of CEs however given the borderline statistical significance (HR = 1.01) these results should be interpreted with caution when considering frequency of cardiac monitoring. Our results are consistent with findings from the Dutch group which observed that older age and a baseline reduced LVEF increased the risk of severe cardiotoxicity ( 21 ).…”
Section: Discussionsupporting
confidence: 93%
“…In this retrospective population-based study of HER2 + aBC, the incidence of cardiac events during or after trastuzumab-based therapy was 7.3%, ( n = 167) with heart failure representing the majority of these events (6.9%, n = 158). These findings are similar to the 3–7% reported in the literature ( 6 , 8 , 14 ), but lower than a Dutch study of 429 patients likely given the reported combined incidence of severe and non-severe cardiotoxicity based on LVEF parameters of 11.7% and 9.1% after 1 and 2 years of trastuzumab respectively ( 21 ); after 4 years of treatment, the cumulative incidence of severe cardiotoxicity (LVEF < 40%) was 3.1%.…”
Section: Discussionsupporting
confidence: 83%
“…Adapting the surveillance approach and frequency according to risk stratification would be expected to reduce the frequency or even omit long-term follow-up in selected very low-risk patients. Bouwer et al investigated cardiotoxicity during long-term trastuzumab use in breast cancer patients, and found that in nonsmoking patients with baseline LVEF >60% and without cardiotoxicity during trastuzumab treatment, the cumulative incidence of severe cardiotoxicity was low, and that serial cardiac monitoring could be omitted safely (35). Thus, using current multiple treatment modalities related to CV toxicity, a CO team could identify who does or does not need cardiac monitoring, and improve the use of clinical resources.…”
Section: Discussionmentioning
confidence: 99%